Pengaruh Pembelajaran Berbasis Inquiry dan Faktor Usia serta Motivasi terhadap Hasil Belajar Mahasiswa UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan - Elastari Matondang, Silvia (Jurnal Inovasi Pendidikan Sains dan Terapan (INTERN ), 2023)
Student learning outcomes can be influenced by internal and external factors. The purpose of this study was to determine the increase in student learning outcomes with inquiry-based learning and the effect of age and motivation on learning outcomes. The research population was all students of chemical tadris who were taught atomic structure in the even semester of the 2022/2023 academic year. The sample of this research was all chemistry students at UIN Syekh Ali Hasan Ahmad Addry Padangsidimpuan with a total of 23 students. Analysis of research instruments and testing the research hypothesis using the SPSS 22 for windows program. The results showed that student learning outcomes increased with learning inquiry and age and motivation factors did not affect student learning outcomes where Sig. (2-tailed) > α (0.938 > 0.05) and (0.513 > 0.05) means that the hypothesis is rejected with a significant level of 5%.